Determinants of Employee Job Satisfaction: A Systematic Literature Review - Handika Eka Pratama; Rizal Ramdan Padmakusumah (Darul Yasin Al Sys, 2026)
Although employee job satisfaction has received increasing attention in prior studies, research that systematically synthesizes its determinants across sectors and contexts remains limited. This study aims to systematically review and integrate empirical evidence on the key determinants of employee job satisfaction reported in Scopus-indexed journals. A systematic literature review approach was employed, guided by the PRISMA framework to identify, screen, and analyze relevant studies. The review was based on 20 empirical articles published between 2015 and 2025, retrieved exclusively from the Scopus database using predefined inclusion and exclusion criteria. Data were collected through a structured literature search and analyzed using qualitative content analysis to identify recurring themes and patterns. The findings indicate that organizational-level and job-related determinants, including leadership practices, perceived organizational support, human resource management systems, workload, job design, and work–life balance are the most influential factors shaping employee job satisfaction, whereas individual-level determinants such as age, tenure, and education exhibit less consistent and more context-dependent effects. These findings contribute to the theoretical development of job satisfaction research by integrating fragmented empirical evidence into a coherent multilevel framework and by highlighting the structural and organizational conditions under which satisfaction is most likely to occur. The study concludes that organizational systems and job structures play a crucial role in enhancing employee job satisfaction and recommends that organizations prioritize supportive leadership, fair human resource practices, and effective job design. The implications of this research include theoretical contributions to the literature on organizational behavior and practical recommendations for managers and policymakers seeking to improve employee well-being and organizational performance, while also identifying opportunities for future research on longitudinal analysis, cross-sector comparisons, and emerging work arrangements such as remote and hybrid work.